2022
DOI: 10.1039/d2sm00067a
|View full text |Cite
|
Sign up to set email alerts
|

The role of the molecular weight of the adsorbed layer on a substrate in the suppressed dynamics of supported thin polystyrene films

Abstract: The adsorbed layer at a solid surface plays a crucial role in the dynamics of nanoconfinement polymer materials. However, the influence of the adsorbed layer is complex, and clarifying this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…This approach or very similar methods have been widely used in the characterization of T g by ellipsometry. 3,4,[6][7][8][9][10][11]13,24,27,[31][32][33][34][36][37][38][39][40][41]56,57,61,62 As shown in Figure 1A, the T g for a 15-nm-thick PS film is ∼90 °C, which is ∼10 °C lower than the T g of a bulk, 350-nm-thick PS film. This result is in reasonable accord with other ellipsometry-based determinations of PS T g -confinement effects 3,6,9,10,13,15,23,[31][32][33][34][36][37][38][39][40]45 and can be explained as originating with a free-surface effect.…”
Section: T G -Confinement Effects Measured By Ellipsometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach or very similar methods have been widely used in the characterization of T g by ellipsometry. 3,4,[6][7][8][9][10][11]13,24,27,[31][32][33][34][36][37][38][39][40][41]56,57,61,62 As shown in Figure 1A, the T g for a 15-nm-thick PS film is ∼90 °C, which is ∼10 °C lower than the T g of a bulk, 350-nm-thick PS film. This result is in reasonable accord with other ellipsometry-based determinations of PS T g -confinement effects 3,6,9,10,13,15,23,[31][32][33][34][36][37][38][39][40]45 and can be explained as originating with a free-surface effect.…”
Section: T G -Confinement Effects Measured By Ellipsometrymentioning
confidence: 99%
“…The glass transition temperature, T g , is a key characteristic of polymer materials because many physical and mechanical properties change markedly when a polymer undergoes a glass transition from a rubbery state to a glassy state or vice versa. , For polymer films confined at the nanoscale, perturbations originating at the polymer/free surface and the polymer/solid interfaces often result in deviations of the measured T g from the bulk T g . Such nanoconfinement behavior is important because it can affect the commercial application of ultrathin polymer films and may aid in understanding the underlying mechanisms of glass transition behavior, which has been a long-standing, unresolved challenge. Indeed, the T g -confinement behavior of polymers has been the subject of intense research since 1994 when Keddie et al , first reported that, relative to bulk T g , the T g s of polystyrene (PS) and poly­(methyl methacrylate) ultrathin films supported on silicon decrease and increase, respectively, with decreasing nanoscale thickness.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,8,14 Moreover, experiments speculated that the adsorption layer affects the glass transition of the polymer thin film through entanglement between loops and non-adsorbed chains. 9–11 Molecular dynamics (MD) simulation proved that entanglement between the loop and free chains inhibits the motion of free chains. 15…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of polymers plays a very important role in the stability of colloidal particles, 1,2 nanoscale surface modification, 3,4 antifouling, 5,6 adhesiveness 7,8 and glass transition temperature of polymer films. [9][10][11] The adsorbed chains usually have three kinds of structures: train, loop, and tail, corresponding to continuously adsorbed segments, segments between two adsorbed trains, and non-adsorbed segments at chain's end, respectively. 12 In a substrate-supported polymer film, there is an adsorption layer which consists of a dense flat adsorption layer dominated by trains and an extended layer dominated by loops and tails.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation